2015
DOI: 10.1089/acm.2014.0281
|View full text |Cite
|
Sign up to set email alerts
|

Are Mindfulness and Self-Compassion Associated with Sleep and Resilience in Health Professionals?

Abstract: Objectives: To describe the relationship between trainable qualities (mindfulness and self-compassion), with factors conceptually related to burnout and quality of care (sleep and resilience) in young health professionals and trainees. Design: Cross-sectional survey. Setting: Large Midwestern academic health center. Participants: 213 clinicians and trainees. Outcome measures: Sleep and resilience were assessed by using the 8-item PROMIS Sleep scale and the 6-item Brief Resilience Scale. Mindfulness and self-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
123
2
13

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(155 citation statements)
references
References 52 publications
17
123
2
13
Order By: Relevance
“…Eleven empirical studies (Heffernan, Quinn Griffin, McNulty, & Fitzpatrick, ; Crarey, ; Senyuva, Kaya, Isik, & Bodur, ; Olson & Kemper, ; Olson, Kemper, & Mahan, ; Finlay‐Jones, Rees, & Kane, ; Kemper, Mo, & Khayat, ; Beaumont, Durkin, Hollis Martin, & Carson, ; Duarte, Pinto‐Gouveia, & Cruz, ; Durkin, Beaumont, Hollins Martin, & Carson, ; Montero‐Martin et al., ) reported on self‐compassion utilising a healthcare provider sample (Table ). Among these, eight studies investigated the role of self‐compassion on work‐related stress among healthcare providers (Crarey, ; Finlay‐Jones et al., ; Kemper et al., ; Olson et al., ; Beaumont et al., ; Duarte et al., ; Durkin et al., ; Montero‐Martin et al., ), and three studies reported on the positive impact of mindfulness and self‐compassion on healthcare provider resilience (Olson & Kemper, ; Olson et al., ; Kemper et al., ). Resilience, the process of coping with or overcoming exposure to adversity (Egeland, Carlson, & Sroufe, ), is considered a salient mitigator of burnout in healthcare providers (Weidlich & Ugarriza, ).…”
Section: Resultsmentioning
confidence: 99%
“…Eleven empirical studies (Heffernan, Quinn Griffin, McNulty, & Fitzpatrick, ; Crarey, ; Senyuva, Kaya, Isik, & Bodur, ; Olson & Kemper, ; Olson, Kemper, & Mahan, ; Finlay‐Jones, Rees, & Kane, ; Kemper, Mo, & Khayat, ; Beaumont, Durkin, Hollis Martin, & Carson, ; Duarte, Pinto‐Gouveia, & Cruz, ; Durkin, Beaumont, Hollins Martin, & Carson, ; Montero‐Martin et al., ) reported on self‐compassion utilising a healthcare provider sample (Table ). Among these, eight studies investigated the role of self‐compassion on work‐related stress among healthcare providers (Crarey, ; Finlay‐Jones et al., ; Kemper et al., ; Olson et al., ; Beaumont et al., ; Duarte et al., ; Durkin et al., ; Montero‐Martin et al., ), and three studies reported on the positive impact of mindfulness and self‐compassion on healthcare provider resilience (Olson & Kemper, ; Olson et al., ; Kemper et al., ). Resilience, the process of coping with or overcoming exposure to adversity (Egeland, Carlson, & Sroufe, ), is considered a salient mitigator of burnout in healthcare providers (Weidlich & Ugarriza, ).…”
Section: Resultsmentioning
confidence: 99%
“…The overall effect size for this outcome was small ( d = .21). Meanwhile, Kemper, Mo, & Khayat () observed a correlation with mindfulness.…”
Section: Discussionmentioning
confidence: 97%
“…Respecto al desarrollo de sĂ­ntomas psiquiĂĄtricos cuando las personas experimentan los eventos estresantes de la vida, la mayorĂ­a de los estudios concluyen que los niveles mĂĄs altos de resiliencia ejercen un efecto protector, ya que no se producen cambios en los sĂ­ntomas psiquiĂĄtricos, se emplean estrategias de afrontamiento mĂĄs efectivas y mayores niveles de afecto positivo (Burton, Pakenham, & Brown, 2009;Hjemdal, Friborg, Stiles, Rosenvinge, & Martinussen, 2006;Maguen et al, 2008;Steinhardt & Dolbier, 2008), correlacionando con niveles mĂĄs bajos de estrĂ©s y mejor salud mental (Kemper, Mo, & Khayat, 2016). Kim, Park, & Kwon (2015), llevaron a cabo un estudio en una muestra de enfermeras, en el que observaron que el sĂ­ndrome del profesional quemado correlaciona negativamente con los niveles de resiliencia y la capacidad de resoluciĂłn de problemas sociales.…”
Section: Resiliencia Y Salud Mentalunclassified